The effect of the degree of solvency commitment on the size of reinsurance risks. "A case study of the United Insurance Company in Syria" (Journal of Hama University, 2021)
The study aims to find out the effect of the degree of adherence to solvency on the size of reinsurance risks in the United Insurance Company listed on the Damascus Stock Exchange. The degree of commitment to solvency in the size of reinsurance risks. And studying the three financial solvency indicators according to the solvency margin system in the Syrian insurance companies issued by the Insurance Supervision Authority Resolution No. 210 of 2008, where the decision specified the necessity of applying these indicators in the first four years of the company's operation only. Only committed values were studied and non-obligated values of solvency indicators were excluded. The study found a positive impact of the degrees of compliance with the first and second indicators of financial solvency on the size of reinsurance risks, and the presence of a negative impact of the degrees of compliance with the third indicator of financial solvency on the size of reinsurance risks. The study recommends that the first and second indicators of financial solvency should be reduced when reinsurance risks increase. And increase the technical allocations to meet the risks of reinsurance.